Pengaruh Ukuran Biochar Bambu dan Dosis Pupuk Urea terhadap Efisiensi Pupuk dan Hasil Tanaman Sawi Hijau (Brassica juncea L.) pada Tanah Berpasir - ANAK AGUNG GDE PREHATRESNA ADI ASMARA; I WAYAN DANA ATMAJA; ANAK AGUNG NGURAH GEDE SUWASTIKA; ANAK AGUNG ISTRI KESUMADEWI (Agrotrop : Journal on Agriculture Science, 2021)
The Effect of Bamboo Biochar Size and Urea Fertilizer Dosage on Fertilizer Efficiency and Yield of Green Mustard (Brassica juncea L.) in Sandy Soil. Biochar is charcoal produced from incomplete combustion (carbonization). Biochar is a soil amendment agent that has long been known in agriculture which is useful for increasing soil productivity. This study aims to determine the effect of bamboo biochar size and urea fertilizer dosage on the efficiency of urea fertilizer and yield of green mustard (Brassica juncea L.). This research was conducted from May 2020 to September 2020 at the Experimental Garden of the Faculty of Agriculture, and at the Laboratory of Soil and Environmental Sciences, Faculty of Agriculture, Udayana University. The research design used was a completely randomized design (CRD) with 2 factorials and 3 replications. The treatment factors consisted of P0 = 0kg urea (control) (0 grams / pot), P1 = 100kg urea / ha (0.2 grams / pot), P2 = 200kg urea / ha (0.4 grams / pot), P3 = 300kg urea / ha (0.6 gram / pot), B1 = 0.25-2.00 mm, B2 = 2.38-2.83 mm, B3 = 2.83-3.36 mm. The parameters observed were levels of ammonium, nitrate, soil pH, microbial population, soil respiration, crop yields including fresh weight and oven dry weight of the plant. The results of the analysis showed that the effect of biochar and urea fertilizers interacted very significantly with the parameters of the microbial population and had no significant effect on the parameters of ammonium, nitrate, soil pH, soil respiration, plant fresh weight, plant dry weight, root fresh weight, root dry weight and efficiency. fertilizer. Biochar treatment has a significant effect on biological factors and fertilizer treatment affects soil chemical properties, crop yields are influenced by a single factor.